Photothermal Fibrous Chitosan/Polydopamine Sponge for Intraoperative Hemostasis and Prevention of Tumor Recurrence in Hepatocellular Carcinoma Resection - Mu, Lanxin; Qi, Luhe; Long, Haitao; Huang, Jing; Zhong, Zibiao; Shi, Xiaowen; Chen, Chaoji; Ye, Qifa (Advanced science, 2024)
Hepatectomy, a surgical procedure for liver cancer, is often plagued by high recurrence rates worldwide. The recurrence of liver cancer is primarily attributed to microlesions in the liver, changes in the immune microenvironment, and circulating tumor cells in the bloodstream. To address this issue, a novel intervention method that combines intraoperative hemostasis with mild photothermal therapy is proposed, which has the potential to ablate microlesions and improve the immune microenvironment simultaneously. Specifically, the integrated strategy is realized based on the fibrous chitosan/polydopamine sponge (CPDS), which is constructed from shearing‐flow‐induced oriented hybrid chitosan fibers and subsequent self‐assembly of polydopamine. The CPDS demonstrates high elasticity, excellent water absorption, and photothermal conversion performance. The results confirm the efficient hemostatic properties of the fibrous CPDS in various bleeding models. Notably, in subcutaneous and orthotopic postoperative recurrence and metastasis models of hepatocellular carcinoma, the fibrous CPDS significantly inhibits local tumor recurrence and distant metastasis. Moreover, the combination with lenvatinib can substantially enhance the antitumor effect. This comprehensive treatment strategy offers new insights into hepatectomy of liver cancer, representing a promising approach for clinical management. A photothermal fibrous chitosan/polydopamine sponge, constructed from shearing‐flow‐induced oriented hybrid chitosan fibers, is presented to enhance hepatectomy outcomes by combining intraoperative hemostasis with mild photothermal therapy. This strategy efficiently addresses bleeding, inhibits tumor recurrence and metastasis in various models, particularly when combined with lenvatinib, offering significant promise for improving liver cancer surgery.